Effects of work environment variables on Chinese prison staff organizational commitment - Jiang, Shanhe (The Australian and New Zealand journal of criminology, 2018)
Staff are critical for the proper functioning of a prison; empirical research into the forces that affect salient organizational attitudes of staff, such as organizational commitment, is equally important. A survey instrument measuring affective commitment and personal (i.e. gender, tenure, age, and educational level), job (i.e. perceived dangerousness of the job, job variety, and supervision), and organizational variables (i.e. instrumental communication and input into decision-making) was completed by 322 employees in two prisons in southern China. The results of ordinary least squares regression showed that job and organizational variables of perceived dangerousness of the job, job variety, supervision, instrumental communication, and decentralization explained 54% of the variance in the dependent variable organizational commitment and were much stronger predictors than personal characteristics. Among the significant variables, decentralization had the largest sized effect, followed by perceived job dangerousness, job variety, and instrumental communication. Except for the organizational variable of perceived supervision quality, the job and organizational predictors of affective commitment for these Chinese prison staff appear to mirror those typically found for staff in US prisons.